Expression of Mutant Ubiquitin and Proteostasis Impairment in Kii Amyotrophic Lateral Sclerosis/Parkinsonism-Dementia Complex Brains - Verheijen, Bert M; Morimoto, Satoru; Sasaki, Ryogen; Oyanagi, Kiyomitsu; Kokubo, Yasumasa; Kuzuhara, Shigeki; van Leeuwen, Fred W (Journal of neuropathology and experimental neurology, 2020)
Abstract Kii amyotrophic lateral sclerosis/parkinsonism-dementia complex (ALS/PDC) is a progressive neurodegenerative disorder that is endemic to the Kii peninsula of Japan. The disorder is clinically characterized by a variable combination of parkinsonism, dementia, and motor neuron symptoms. Despite extensive investigations, the etiology and pathogenesis of ALS/PDC remain unclear. At the neuropathological level, Kii ALS/PDC is characterized by neuronal loss and tau-dominant polyproteinopathy. Here, we report the accumulation of several proteins involved in protein homeostasis pathways, that is, the ubiquitin-proteasome system and the autophagy-lysosome pathway, in postmortem brain tissue from a number of Kii ALS/PDC cases (n = 4). Of particular interest is the presence of a mutant ubiquitin protein (UBB+1), which is indicative of disrupted ubiquitin homeostasis. The findings suggest that abnormal protein aggregation is linked to impaired protein homeostasis pathways in Kii ALS/PDC.